(untitled) - Leider, Colby (New York, 2004)
Digital audio workstation are not only revolutionizing the way music is recorded, but allow new forms of electronic music, created entirely in the computer, to be written and recorded on the desktop. The Digital Audio Workstation Studio, by renowned digital music expert Colby Lieder, will be the first book to teach the complete DAW process, from outfitting your computer with the necessary hardware and software, recording with the proper microphones, using DAW power to create perfectly modulated mixes, to finally mastering down into a completely professional finished product. With this book, a computer, and a little imagination, any musician can create utterly professional music CDs, DVDs, or streamed audio.
Keywords: Sound,Music; Recording and reproducing,Digital techniques,Editing,Data processing